Further faster : the ultimate guide to accelerating your career - James, Warren ([Milton, Queensland] : Rapid Mentoring, 2020)
“You too can find direction and build a roadmap to take your life and career further faster, even if right now you are feeling a little underequipped for the journey ahead. Come on a journey of self-discovery with Warren James. The Rapid Mentor, to uncover: - Who you are and where you want to go. – The pillars you can use to build your own robust, balanced lifestyle. – The tools you need to succeed at any level in life. – How to easily master the life skills that everyone else will learn the hard way. – The strategies you need to help accelerate your journey and get you where you want to be faster.”--Back cover.
Includes QR code.
Includes bibliographical references (pages 197-198)
Keywords: Career development -- Handbooks, manuals, etc; Australian